Моделі та методи кубітного тестування цифрових пристроїв на основі memory-driven структур даних - Ємельянов, І. В. (My University, 2018)
Мета дослідження – розробка квантових методів паралельного синтезу та аналізу цифрових пристроїв і компонентів для істотного підвищення швидкодії програмних хмарних сервісів і зменшення часу проектування програмно-апаратних комп’ютингових систем за рахунок збільшення пам'яті для зберігання кубітних структур даних. Основні результати: модель метричної взаємодії класичного та квантового комп'ютингу, яка характеризується взаємно- днозначною відповідністю за параметрами паралелізму, суперпозиційності та переплутування в обох видах обчислень, що дає можливість реалізувати квантовий комп'ютинг в класичному виконанні за рахунок збільшення пам'яті; метод невизначених коефіцієнтів для мінімізації булевих функцій, який відрізняється від класичного унітарним кодуванням даних для паралельного виконання логічних операцій в цілях отримання двох векторів, відповідних мінімальній диз'юнктивній і кон'юнктивній нормальним формам; кубітний метод пошуку дефектів, який відрізняється від існуючого унітарним кодуванням таблиці дефектів, що перевіряються, для паралельного виконання операцій; квантовий метод синтезу тестів для логічних функціональностей за рахунок використання булевих похідних за змінними на кубітних структурах даних; квантовий метод моделювання справної поведінки за рахунок memory-driven реалізації кубітних структур даних, що дає можливість використовувати транзакційні адресно-орієнтовані процедури аналізу цифрових пристроїв, які виключають логічні операції. The goal of the investigation is to develop quantum methods for parallel synthesis and analysis of digital devices and components to significantly improve the performance of cloud software services and reduce the design time of software and hardware computing systems through increasing memory for storing qubit data structures. The main results are the following: 1) a new model of the metric interaction of classical and quantum computing, which is characterized by a one-to-one correspondence of the parameters of parallelism, superposition and entanglement in both types of computing; this makes it possible to realize quantum computing in the classical execution through increasing the memory; 2) an improved method of undetermined coefficients for minimizing Boolean functions, which differs from the classical one by unitary coding of data for parallel execution of logical operations in order to obtain two vectors corresponding to the minimal disjunctive and conjunctive normal forms; 3) an improved qubit method of fault detection, which differs from the existing one by unitary encoding of the fault detection table for parallel execution of operations, which makes it possible to reduce the calculations to the logical difference of two vectors corresponding to the unit and zero values of states-responses of the digital device outputs during the test experiment; 4) a quantum method for test synthesis of logical functionalities has been further developed through the use of Boolean derivatives with respect to variables on qubit data structures, which makes it possible to increase the performance of the method through the parallel execution of logical operations; 5) a quantum method for fault-free simulation is further developed through the memory-driven implementation of qubit data structures, which makes it possible to use transactional address-focused procedures for analyzing digital devices free of logical operations.
Keywords: кубіт; кубітне покриття; квантове проектування; моделювання і тестування; верифікація; діагностування; memory-driven кубітні структури даних; цифрові системи на кристалах; квантові обчислення; qubit; qubit coverage; quantum design; simulation and test; verification; diagnosis; memory-driven qubit data structures; digital system-onchip; quantum computing